Heathers (Erica, Ericaceae) of Madagascar: taxonomy, evolution, ecology and uses - Jan Hackel; Andriantsilavo H. I. Razafimanantsoa; Vincent Porcher; Michael D. Pirie (PhytoKeys)
The plant genus Erica L. (heathers; anjavidy in Malagasy) has 35 recognised species in Madagascar, but there has not been a taxonomic revision since 1927 and there are few identification resources. We review available data for Malagasy Erica (previously treated as Philippia), summarise diagnostic species descriptions and incorporate them into the Erica Identification Aid. There is clearly variation in current species concepts that requires further study. Malagasy Erica most likely represent a single clade also encompassing species from the Mascarenes, but resolution is poor and most species remain unsequenced. Erica is found in several of Madagascar’s ecosystems, including the high-altitude “ericoid thickets” where diversity is highest, but it is absent from the extensive dry western areas. Habitats include the ericoid thickets, shrubland–grassland mosaics in the central highlands and on the eastern coast, and Uapaca bojeri (tapia) savanna. Many Erica species are likely to be part of dynamic ecosystems with infrequent fire regimes. The palaeorecord indicates a more widespread ericoid shrub vegetation during the last glacial period. There may be both wind- and insect-pollinated species. Erica is mainly used as fuelwood in Madagascar, but local uses as tools and medicine have also been reported. Estimates suggest at least one-fifth of the species may be threatened, but formal assessments are lacking. Taxonomic revision of the group, coupled with phylogenomic, ecological and ethnobotanic studies, is an urgent priority.